PERLINDUNGAN HUKUM BAGI REMAJA PEREMPUAN DARI KEKERASAN SEKSUAL VIA MEDIA SOSIAL - Syaharani, Nabilah; Rahmayanti, Rahmayanti; Nurdiana, Citra; Saputra, Defri Dwi; Harahap, Rizki Nanda Fauzi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2025)
Technological advancements have significantly transformed modes of communication in society, particularly among adolescents. Social media has become the primary space for interaction; however, it also presents negative impacts, one of which is online-based sexual violence. Adolescent girls are the most vulnerable group to such violence due to their psychological and social conditions, which are still in developmental stages. This study aims to analyze the forms of sexual violence perpetrated through social media and to assess the effectiveness of existing legal protections available for adolescent girls as victims. The research employs a normative juridical method with statute and conceptual approaches. The findings indicate that digital sexual violence—including the non-consensual dissemination of intimate content, cyberstalking, and sexually charged comments—constitutes criminal acts punishable under the Sexual Violence Crimes Law (UU TPKS), the Electronic Information and Transactions Law (UU ITE), and the Indonesian Penal Code (KUHP). However, weak law enforcement and prevailing victim-blaming culture exacerbate the victims' conditions. Prevention must be pursued collaboratively through digital literacy education, community empowerment, the establishment of safe reporting mechanisms, and firm legal enforcement. Social media must be managed as a safe and equitable space, rather than a platform for exploitation.